Analysis of Student Understanding Department of Sharia Accounting Faculty of Economics and Islamic Business IAIN Lhokseumawe on the Basic Concepts of Accounting - Muhamad Syafril Nasution; Almira Keumala Ulfah; Ramadhan Razali (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The basic concept of Accounting is an urgent and basic subject that must be known by students, especially students majoring in Islamic accounting. The basic concept of Accounting is studied by students for two semesters in the accounting introduction course. The purpose of this research is to find out the extent of the understanding of students majoring in Sharia Accounting in understanding the basic concepts of accounting. The method used in this study is the mix method. While the results found are: first, students still lack understanding about the terms of basic accounting concepts. In addition, students also lack understanding about the method of calculation in accounting. Second, the knowledge of accounting in students has an effect on understanding the basic concepts of accounting in students. Third, the interest in studying accounting in students affects the understanding of basic accounting concepts in students. Third, the teaching style of lecturers introducing accounting has an effect on understanding the basic concepts of accounting that exist in students.